Integrated Geological and Geoelectrical Investigation of Groundwater Potential in Part of Sheet 54 SE (Gusau SW), Zamfara State, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study presents the results of detailed geological mapping and geoelectrical investigation carried out in Sheet 54SE (Gusau SW), Zamfara State, northwestern Nigeria, with the objective of characterizing lithological units, structural features, and evaluating groundwater potential within the crystalline basement terrain. Geological field mapping involved systematic in-situ examination of rock outcrops, structural measurements, and lithological identification. The area is characterized by low-lying ridges and whaleback exposures dominated by coarsegrained granitic rocks. Structural features mapped include joints, faults, quartz vein intrusions, and zones of differential weathering, all of which play a significant role in controlling secondary porosity and permeability within the basement rocks. Petrographic analysis of representative rock samples under plane-polarized light (PPL) and cross-polarized light (XPL) reveals that the granites are predominantly composed of quartz, orthoclase, biotite, and hornblende, confirming their affinity with the Pan-African granites widely distributed across northwestern Nigeria. Groundwater potential was further evaluated using the Vertical Electrical Sounding (VES) technique with the Schlumberger electrode configuration and a maximum current electrode spacing (AB/2) of 100 m. A total of fifteen VES stations were occupied along five traverses across the study area. Interpretation of the geoelectrical data delineated three to four subsurface geoelectric layers comprising topsoil, weathered basement, fractured basement, and locally fresh basement. The topsoil layer exhibits thicknesses ranging from 0.545 to 20 m with resistivity values of 15.6–39 Ωm, while the weathered basement layer varies between 0.758 and 60 m with resistivity values of 34.4146.6 Ωm. The fractured basement layer occurs at depths of 23–93 m and displays resistivity values of 161.2–408.9 Ωm. The weathered and fractured basement horizons constitute the principal aquifer units in the area. Among the sounding locations, VES 4, VES 5, and VES 6 exhibit the most promising groundwater potential due to their relatively thick conductive weathered zones and well-developed fractured basement. The results demonstrate that integrated geological and geoelectrical investigations provide a reliable approach for groundwater exploration and aquifer delineation in crystalline basement terrains.